Development of a multiyear pediatric antibiogram in Georgia identifies antibiotic resistance trends - Matt Linam; Madeleine Goldstein; Robert Jerris; Mark Gonzalez (Cambridge University Press, 2023)
Background: Antibiograms are used to monitor antibiotic resistance trends and help guide empiric antibiotic treatment. Community pediatricians may not have access to or be comfortable using children's hospital antibiograms. Creating and disseminating a statewide pediatric antibiogram can help inform antibiotic stewardship efforts.